Age-related hearing loss and its association with central obesity: experience at a tertiary centre - Agrawal, Utkarsh; Singh, Anjali; Chaudhary, Ashvanee; Singh, Vishwambhar (International Journal of Research in Medical Sciences, 2020)
Background: Presbycusis is a slow, progressive, age-related sensorineural hearing loss, which is insidious, slow, progressive and irreversible disease and usually affects high pitch sound. It can be associated with various factors. Obesity is such a modifiable factor and its independent role with age-related hearing loss needs to be explored. Methods: This is a prospective study carried out over a period of three years in department of otorhinolaryngology at study institute. It included 1000 cases with symmetrical sensorineural hearing loss. Results: Among obese cases, high frequency hearing loss was found in significantly large number of cases. The most common audiogram in both male and female was Abrupt high tone loss type, irrespective of presence or absence of obesity. Conclusions: Obesity is a modifiable factor which has a significant association with high frequency hearing loss among the elderly population.